PENGARUH PROFITABILITAS DAN SALES GROWTH TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN SUBSEKTOR FARMASI - Cut Widy Aulia Putri; Abrar Amri (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the extent to which the two variables profitability and sales growth affect the probability of experiencing financial distress among pharmaceutical companies listed on the Indonesia Stock Exchange during the period 2021 to 2024. Purposive sampling was used to purposefully select companies that met the predetermined criteria, and a total of eight companies were selected as a sample. In order to test the proposed hypotheses, this study used multiple regression analysis as a statistical method to evaluate the partial effects of independent variables on financial distress. The results of the analysis found that profitability had a statistically significant effect on the probability of a company experiencing financial distress. In contrast, sales growth had no significant or meaningful effect on the financial stress of the companies studied. Keyword: Financial distress; Profitability; ROA; Sales Growth